Key Support Persons of Counselling Programs in Indonesian Vocational High School - Satrio Budi Prakoso (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
The counselling program contributes to school achievement by promoting character development and teaching social behaviours. In Indonesia, particularly in vocational high schools, the provision of counselling services is still unsatisfactory and requires improvement, but studies on the implementation of such services are currently lacking. I collected data at a vocational high school in Indonesia by interviewing a school counsellor, a subject teacher and students about the implementation of counselling services and the personal support offered by these programs. The results showed that implementing counselling services in vocational high schools in Indonesia has a positive effect. The headteacher, form tutors, subject teachers, counsellors and parents of students suggested collaborating and communicating in counselling service programs. Therefore, this study strongly supports the sufficient application of counselling services in vocational high schools in Indonesia, requiring personal support from those involved in improving academic performance and behaviour of student.